Adults with Phenylketonuria have suboptimal bone mineral density apart from vitamin D and calcium sufficiency - Hanusch, Beatrice; Schlegtendal, Anne; Grasemann, Corinna; Lücke, Thomas; Sinningen, Kathrin (Frontiers in Endocrinology, 2025)
IntroductionImprovement of early diagnosis and treatment in patients with Phenylketonuria (PKU) allowed for healthy survival into adulthood of these patients, but non-neurological health impairments of unknown etiology emerged. One of these is impaired bone health that manifests in adolescence and adulthood, potentially depending not only on treatment adherence but also on additional lifestyle factors and nutrition.MethodsEighteen adults with PKU (18.3–51.6 years, ♀ n = 11) and 19 age- and gender-matched controls (18.3–54.9 years, ♀ n = 10) participated in the study. Bone metabolism–related parameters (BMRPs) in plasma, serum, and urine were analyzed. Dietary habits and lifestyle factors were obtained from questionnaires; a 6-min walk test and a dual X-ray absorptiometry measurement at two sites were performed. Phenylalanine (Phe) serum concentrations from the 5 years prior to study participation were collected from the patients’ charts.ResultsPatients had reduced bone mineral density (BMD) T-score in hips (−0.67 ± 1.05) and lumbar spine (−0.71 ± 1.11, both p = 0.018). Most BMRPs in plasma, serum, and urine, as well as markers of oxidative stress did not differ from healthy controls. Whereas 89% of adults with PKU were vitamin D–sufficient, only 68% of controls reached vitamin D sufficiency. 25-Hydroxy vitamin D concentration was significantly higher in adults with PKU than that in controls [33.1 ng/mL (26.2–40.3) vs. 23.4 ng/mL (17.2–24.9); p < 0.001], whereas parathyroid hormone concentrations showed no difference [PKU: 27.6 pg/mL (19.6–42.8) vs. Co: 36.1 pg/mL (29.2–40.8); p = 0.089]. Neither Phe blood concentration nor dietary habits or lifestyle factors were associated with BMD in regression analysis.ConclusionNeither dietary habits nor lifestyle factors showed an association with BMD in this group of adults with PKU, whereas BMD was reduced.